A key to Siberian flies of the genus Coenosia Meigen (Diptera, Muscidae) with the descriptions of three new species - Sorokina, Vera S. (Zootaxa, 2009)
A key is provided to the 36 species of the genus Coenosia Meigen, 1826 known from Siberia including three new species from the Respublika Altay (Coenosia altaica sp. nov., Coenosia tangera sp. nov., Coenosia ukokensis sp. nov.) and one additional Far East species that may be found in Siberia (Coenosia nigrotincta Hennig). Coenosia alpicola (Pokorny) is newly recorded from Siberia, and also represents a new record from Russia. Coenosia apukаensis Hennig and Coenosia rufipalpis Meigen are newly recorded from Siberia. The male terminalia and the female ovipositors of the new species are figured. New faunistic data is given for some previously described species of Siberian Coenosia.